Effect of sublethal unionized ammonia on mortality rate of red tilapia (Orepchromis Spp.) fingerlings in Aeromonas hydrophila infection. - Zainal, Nurul Faizah; Mutalib, Abdul Rahim; Matori, Mohd Fuat; Omar, Mohamed Ariff (2011)
A study was carries out to investigate the effect of sublethal unionized ammnonia concentraction on the mortality rate of tilapia fingerlings in Aeromonas hydrophila infection. Mono-sex tilapia about 5 cm in length was used in this experiment. Sublethal unionized ammonia concentrations were determined and 1.1, 1.7, 2.2, 3.6 and 4.6 mg/L ammonium chloride was chosen for the experiment. The sublethal effects of unionized ammonia concentration on A. hydrophila infection in fish fingerlings were then determined. There were 2 mortalities each at ammonia concentrations of 2.2 and 3.6 mg/L in fingerlings infected with A. hydrophila. However, there seemed to be no association between concentration of unionized ammonia and fingerling mortality suggesting that sublethal unionized ammonia concentrations do not cause death in fingerlings exposed to A. hudrophila infection.